2008
DOI: 10.3748/wjg.14.1774
|View full text |Cite
|
Sign up to set email alerts
|

Model for end-stage liver disease score versus Child score in predicting the outcome of surgical procedures in patients with cirrhosis

Abstract: The CTP and MELD scores performed equally, but only fairly in predicting the outcome of urgent surgical procedures. Larger studies are needed to better define the factors capable of predicting the outcome of elective surgical procedures in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 25 publications
1
42
2
4
Order By: Relevance
“…94 In another study, CTP and MELD scores were similar in predicting outcome after elective surgery but only fairly after urgent surgery in cirrhotics. 98 …”
Section: Comparing Model For End-stage Liver Disease and Child-pugh-tmentioning
confidence: 99%
“…94 In another study, CTP and MELD scores were similar in predicting outcome after elective surgery but only fairly after urgent surgery in cirrhotics. 98 …”
Section: Comparing Model For End-stage Liver Disease and Child-pugh-tmentioning
confidence: 99%
“…Likewise, Mansour et al 18 found similar data, with a mortality of 10%, 30% and 82% for groups Child A, B and C, respectively 18 . Using the MELD criterion (Model for End-stage Liver Disease), other authors have also shown an association between worse post-operative outcome in patients with cirrhosis and worsening of their liver function 5,7,911,15,22,28 .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis by Teh et al, showed 772 cirrhotics who underwent major gastrointestinal, orthopedic, or cardiovascular surgery, MELD was a strong predictor of mortality at 30 and 90 days while persisting throughout a 20-year follow-up period [119]. MELD score 0-11 correlated with 5-10% 90-day mortality, 12-25 with 25-54% mortality rate, and ≥26 with a 90% postoperative mortality rate [120,121] (Table 2) [122], resulting in a MELD ≥10 having better Sn while MELD ≥25 with better mortality Sp. This was attributed to several factors including more post-necrotic LC and less cardiovascular surgery cases, whereas Teh's study included more patients with alcoholic cirrhosis with a poorer short term survival, and possible ethnic differences medication tolerance [123].…”
Section: Preoperative Evaluation Of Known Cirrhosismentioning
confidence: 99%